1994
DOI: 10.1136/jme.20.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of women to fetal tissue research.

Abstract: The use of human fetal tissue for scientific research has enormous potential but is subject to government legislation. In the United Kingdom the Polkinghorne Committee's guidelines were accepted by the Department ofHealth in 1990. These guidelines set out to protect women undergoing termination ofpregnancy from exploitation but in so doing may significantly restrict potential research. Although the committee took evidence from a wide variety of experts they did not seek the views of the general public. We aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…The questions on treatment and research using fetal tissue have not yet been asked for general population samples in other countries, so we cannot generalize with any certainty (31). However, Western nations share many social attitudes (32,33) and cross-national data on evolution and abortion (two key influences on attitudes towards the use of fetal tissue), suggest that Australian opinion is similar to that in many other developed nations for which we have data (Fig.…”
Section: Do These Results Generalize To Other Countries?mentioning
confidence: 63%
“…The questions on treatment and research using fetal tissue have not yet been asked for general population samples in other countries, so we cannot generalize with any certainty (31). However, Western nations share many social attitudes (32,33) and cross-national data on evolution and abortion (two key influences on attitudes towards the use of fetal tissue), suggest that Australian opinion is similar to that in many other developed nations for which we have data (Fig.…”
Section: Do These Results Generalize To Other Countries?mentioning
confidence: 63%
“…Notes 1. Of 793 women considering therapeutic abortion, 94% did not have a problem with fetal tissue being used in medical research (Anderson et al 1994); a more recent study showed that women's initial enthusiasm waned when they learned more about the research procedure (Pfeffer 2008 (2005) survey of 2432 adults revealed 68% thought it acceptable to use "spare" embryos up to the 14th day for medical research, but 46% opposed creation of embryos solely for this purpose. 3.…”
Section: Resultsmentioning
confidence: 97%
“…Their opinions were not different from those of surveyed women [23]. According to Anderson et al, 94% of women feel that fetal tissue research was justifiable and 84% say they would allow this sort of research to be done on their own fetus [23].…”
Section: Discussionmentioning
confidence: 99%